EFFECT OF PRICING ON CONSUMER BUYING BEHAVIOR IN CHENGALPATTU TOWN - R. JAGANNATHAN; P. RAVICHANDRAN (International Journal of Psychosocial Rehabilitation, 2025)
The study of Consumer buying behavior is very challenging task. Consumer consider variousfactors when making purchase decisions. If a Company wants to survive, it should be able tocompete well on different factors and the most important one is Price. The main purpose of thisresearch is to measure the effect of pricing strategies on consumers’ psychology and on theirbuying behavior accordingly. A questionnaire has been designed, distributed and filled up by participants from Chengalpattu Town. 125 responses were received from respondents, where SPSS were used to analyze the data collected. The findings show that there is a positive relationship between prices and consumer buying behavior. Depending on the founding results, recommendations were set to retailersand dealers.